“Tertawa” dalam Budaya Jawa: Sebuah Kajian Antropologi Bahasa - Hendarto Supatra (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Human being is the only God’s creation that can tertawa (laugh) and tersenyum (smile). People tertawa or tersenyum when they want to express their happiness, it is at least according to Kamus Besar Bahasa Indonesia (2011) or laugh according to The Macquarie Dictionary (1991). But sometime people also tertawa or tersenyum when they experience serious bad luck. Often people has no choise but tertawa or tersenyum as a way to show their feeling which they don’t think possible to express in verbal language. Tertawa and tersenyum phenomena are universal. But every language has their unique way  to symbolize them. In Indonesian spoken by people with the Javanese culture as their background use severel words and phrases as the synonyms of tertawa to encode many difference experiences which are still with in the concept of tertawa. The goal of this research is to describe the form and behavior the word tertawa and all it’s synonyms and to find out the reasons behind the use of the words or people mean when they use the words. To get the goal fulfilled this research used linguistic anthropology, it’s theories and methods.